Ultrastructural changes on the epithelial cells of uterine tubes of Wistar rats after chronic ethanol ingestion - Martinez, Marcelo; Branco, A. C.; Cagnon, V. H. A.; Mello, W.; Garcia, P. J.; Martinez, F. E. (My University, 1999)
The present paper describes the morphological alterations of the epithelial layer of the uterine tubes of rats submitted to experimental chronic alcoholism using anatomical, histological, ultrastructural and morphometric methods. Sixty adult rats (Rattus norvegicus albinus) at the same age (3 months) and with a mean body weight of 228 g were divided into two groups. The control group received solid diet (Purina rat chow) and tap water ad libitum. The alcoholic group received the same solid diet and was allowed to drink only sugar cane brandy dissolved in 30° Gay Lussac (v/v). After periods of 90, 180 and 270 days of treatment animals at normal estrus were anaesthetised with ethyl ether, weighed and sacrificed. Subsequently, the uterine tubes were dissected, weighed and prepared for TEM and SEM methods. The final mean body weights were similar in the control and alcoholic groups. The morphometric analysis showed no difference between control and alcoholic epithelial height. The alcoholic animals showed ultrastructural alterations: intense lipid droplet and lysosomes accumulation, dilated rough endoplasmic reticulum cisternae and vacuolization in both periods of treatment. It was concluded that alcohol acts as a toxin on the epithelial layer of the uterine tubes of rats.
Keywords: Alcoholism; Epithelium; SEM; Uterine tubes; animal; comparative study; drinking behavior; drug effect; electron microscopy; epithelium cell; female; pathology; rat; time; ultrastructure; uterine tube; Wistar rat; Alcohol Drinking; Animals; Epithelial Cells; Fallopian Tubes; Female; Microscopy, Electron; Rats; Rats, Wistar; Time Factors